A HapMap leads to a Capsicum annuum SNP infinium array: a new tool for pepper breeding. (27th July 2016) - Hulse-Kemp, Amanda M; Ashrafi, Hamid; Plieske, Joerg; Lemm, Jana; Stoffel, Kevin; Hill, Theresa; Luerssen, Hartmut; Pethiyagoda, Charit L; Lawley, Cindy T; Ganal, Martin W; Van Deynze, Allen
Abstract: The Capsicum genus (Pepper) is a part of the Solanacae family. It has been important in many cultures worldwide for its key nutritional components and uses as spices, medicines, ornamentals and vegetables. Worldwide population growth is associated with demand for more nutritionally valuable vegetables while contending with decreasing resources and available land. These conditions require increased efficiency in pepper breeding to deal with these imminent challenges. Through resequencing of inbred lines we have completed a valuable haplotype map (HapMap) for the pepper genome based on single-nucleotide polymorphisms (SNP). The identified SNPs were annotated and classified based on their gene annotation in the pepper draft genome sequence and phenotype of the sequenced inbred lines. A selection of one marker per gene model was utilized to create the PepperSNP16K array, which simultaneously genotyped 16 405 SNPs, of which 90.7% were found to be informative. A set of 84 inbred and hybrid lines and a mapping population of 90 interspecific F2 individuals were utilized to validate the array. Diversity analysis of the inbred lines shows a distinct separation of bell versus chile/hot pepper types and separates them into five distinct germplasm groups. The interspecific population created between Tabasco ( C. frutescens chile type) and P4 ( C. annuum blocky type) produced a linkage map with 5546 markers separated into 1361 bins on twelve 12 linkage groups representing 1392.3 cM. This publically available genotyping platform can be used to rapidly assess a large number of markers in a reproducible high-throughput manner for pepper. As a standardized tool for genetic analyses, the PepperSNP16K can be used worldwide to share findings and analyze QTLs for important traits leading to continued improvement of pepper for consumers. Data and information on the array are available through the Solanaceae Genomics Network. Abstract : Genetic analysis: A hot new tool for pepper breeding A new map showing variable sites in the pepper ( Capsicum ) genome provides a platform to support rapid improvement of the crop. Capsicums, including sweet 'bell' and hot 'chile' types, are an increasingly important crop worldwide. Breeding new varities of pepper requires efficient searching for differences between the genomes of different varieties which might be associated with desirable traits. An international team led by Allen Van Deynze of the University of California-Davis, USA, used new high-throughput 'microarray' technology to generate a map of variable sites known as 'single nucleotide polymorphisms' (SNPs) in the pepper genome. They found almost 15, 000 functional SNPs across both types of pepper. These findings provide an easy-to-use standardized resource for pepper researchers and breeders across the world to discover and exploit the genetic differences associated with economically important traits.